2012
DOI: 10.1089/thy.2011.0439
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse 131I Lung Uptake in Bronchiectasis: A Potential Pitfall in the Follow-Up of Differentiated Thyroid Carcinoma

Abstract: (131)I uptake should be interpreted on the bases of clinical context, imaging, and laboratory findings (serum Tg). Recognition of potential false-positive (131)I scans is critical to avoid unnecessary exposure to further radiation from repeated therapeutic doses of (131)I with possible side effects and even worsening of lung disease itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
(25 reference statements)
0
5
1
Order By: Relevance
“…Diffuse uptake showed a difference from that of bronchiectasis or inactive pulmonary tuberculosis, which demonstrated focal uptake patterns corresponding to pathologic focus [14][15][16]. One previous study reported that diffuse uptake can be seen in bronchiectasis [6]. However, in our study the fact that abnormal chest radiograph findings were Fig.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Diffuse uptake showed a difference from that of bronchiectasis or inactive pulmonary tuberculosis, which demonstrated focal uptake patterns corresponding to pathologic focus [14][15][16]. One previous study reported that diffuse uptake can be seen in bronchiectasis [6]. However, in our study the fact that abnormal chest radiograph findings were Fig.…”
Section: Discussioncontrasting
confidence: 62%
“…Radioactive iodine scans, along with the thyroblobulin (Tg) level, play an important role in the diagnosis of lung metastasis. Diffuse intrathoracic uptake is also known to be observed in other benign lesions [6], as well as lung metastases, but other possible causes are not clearly established. Particular attention must be paid to diffuse intrathoracic uptake on post-therapy scans without specific pathological foci on other imaging studies.…”
Section: Introductionmentioning
confidence: 99%
“…Other etiologies that have been proposed are accumulation of radioiodine in inflamed organs, metabolism of radiodinated thyroid hormone, the presence of radioiodine in body fluids, and therefore contamination by physiologic secretions. Common sites of physiologic ectopic radioactive iodine uptake seen in clinical practice include parotiditis, maxillary abscess, thyroglossal ducts, bronchiectasis, hiatal hernia, esophageal retention, and sebaceous cysts [ 1 , 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In some instances, foci of 131 I activity are not related to the presence of NIS, but due to retention of radioiodine in physiologic body fluids accumulated in ducts or cavities (13,14) as well as contamination by physiologic secretions (5). In addition, it has also reported radioiodine trapping in various inflamed tissues and/or cysts because of their increased vascularity and capillary permeability (15)(16)(17). Finally, in some cases, the mechanism for 131 I trapping remains unknown.…”
Section: Discussionmentioning
confidence: 99%